2009
DOI: 10.1177/1090198109343886
|View full text |Cite
|
Sign up to set email alerts
|

An Urban Food Store Intervention Positively Affects Food-Related Psychosocial Variables and Food Behaviors

Abstract: Obesity and other diet-related chronic diseases are more prevalent in low-income urban areas, which commonly have limited access to healthy foods. The authors implemented an intervention trial in nine food stores, including two supermarkets and seven corner stores, in a low-income, predominantly African American area of Baltimore City, with a comparison group of eight stores in another low-income area of the city. The intervention (Baltimore Healthy Stores; BHS) included an environmental component to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(152 citation statements)
references
References 20 publications
4
141
0
7
Order By: Relevance
“…High levels of consumption of convenience store foods in this sample also warrant exploration of store-based interventions. Programmes including prioritization of shelf space, stocking of fresh produce and product signage/labelling have been shown to hold promise in increasing the purchase and consumption of healthy foods (43,44) . Specific to utilization of food banks, a number of challenges were identified that should be taken into consideration in future programmes and policies on reservations.…”
Section: Implications For Intervention Developmentmentioning
confidence: 99%
“…High levels of consumption of convenience store foods in this sample also warrant exploration of store-based interventions. Programmes including prioritization of shelf space, stocking of fresh produce and product signage/labelling have been shown to hold promise in increasing the purchase and consumption of healthy foods (43,44) . Specific to utilization of food banks, a number of challenges were identified that should be taken into consideration in future programmes and policies on reservations.…”
Section: Implications For Intervention Developmentmentioning
confidence: 99%
“…Such interventions include expanding farmers markets (1), increasing fresh food inventory in small stores (2,3), financing programs to support full-service groceries in underserved communities (4), and initiating healthy vending machine programs (5)(6)(7). Most healthful food interventions focus on school and community settings.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos demonstraram efetividade em suas ações no que diz respeito ao aumento da disponibilidade de alimentos saudáveis e mudanças em fatores psicossociais de consumidores e proprietários de comér-cio, com o aumento na venda de alimentos saudáveis (SONG et al, 2009) e aumento do lucro dos comerciantes com a venda de alimentos saudáveis (AYALA et al, 2012). Efeitos positivos nos parâmetros psicossociais dos comerciantes como aumento da autoeficácia em relação à comercialização e estocagem de alimentos saudáveis (SONG et al, 2009), e também nos dos clientes expostos a intervenção, como aumento de intenções de compras de alimentos saudáveis (GITTELSOHN et al, 2013) e melhora na autoeficácia em cozinhar alimentos saudáveis também foram observados (GITTELSOHN et al, 2010).…”
Section: Introductionunclassified